Nocardia takedensis: a newly recognized pathogen responsible for skin and soft tissue infections - Romain Lotte; Alicia Chevalier; Sabine Dantas; Nicolas Degand; Alice Gaudart; Pierre-Simon Rörhlich; Laurent Boyer; Veronica Rodriguez-Nava; Pascal Del Giudice; Raymond Ruimy (BMC, 2020)
Abstract Nocardia takedensis was first isolated in 2005, from soil in Japan. We report here two cases of lymphangitis in France (2012-2017) caused by N. takedensis both occurring after skin injury while gardening, which enabled its inoculation. The two patients were immunocompromised and successfully treated by an antimicrobial agent active on the isolated strain, trimethoprim-sulfamethoxazole and amoxicillin-clavulanic acid for patient one and patient two, respectively. Our study along with previous ones supports the idea of a newly recognized cutaneous opportunistic pathogen and reinforces the recommendation of using gloves during soil exposure for immunocompromised patients. Lastly, according to data found in the literature, we would recommend trimethoprim-sulfamethoxazole as an efficient empirical antibiotic therapy in case of cutaneous infection caused by N. takedensis.